If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + -5 = -7 + 4p Reorder the terms: -5 + 6p = -7 + 4p Solving -5 + 6p = -7 + 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. -5 + 6p + -4p = -7 + 4p + -4p Combine like terms: 6p + -4p = 2p -5 + 2p = -7 + 4p + -4p Combine like terms: 4p + -4p = 0 -5 + 2p = -7 + 0 -5 + 2p = -7 Add '5' to each side of the equation. -5 + 5 + 2p = -7 + 5 Combine like terms: -5 + 5 = 0 0 + 2p = -7 + 5 2p = -7 + 5 Combine like terms: -7 + 5 = -2 2p = -2 Divide each side by '2'. p = -1 Simplifying p = -1
| 3/4n-24 | | .10x+.25(x+6)+.05*4(x+6)= | | 8n-29=-2+3n | | .75(x-8)=12 | | x+7x+4=180 | | 1384.74=r^2*3.14 | | -13h=6h+114 | | a/5=a-3/5 | | 138.74=r^2*3.14 | | 5(3+5x)-3=137 | | 5y-4=5y+6 | | 2v-19=5v-10 | | 5x^2-3(-2)= | | 4x^2+2x-2=3 | | 6x+y=80 | | 8z+9+-12z=4z+-13+5Z | | (x+m^3)+(x-m^3)=(2x^3)+(12m^3) | | e^6x=15 | | 6(4x-1)=2(12x+8) | | 0.24=logx | | 6(4x-1)*6(x^2-5)= | | 28y+4=47 | | 30-1/24(3x)=20-1/24(2x) | | f(x)=(x^2-18x+81)(x-9) | | -7/8t=1/6 | | -3r+7(-1-4r)=117 | | 25=4+3p | | 8y-4+3y=7y+y+14 | | 6(6x-4)=-96 | | 6x+3(-7x+-16)=-168 | | 5x+9y-3=8y+18-3y | | 15=120+3n |